FORMS OF PRESCHOOL EDUCATIONAL ORGANIZATION WITH FAMILY (World Bulletin of Social Sciences, 2021)
This article describes the forms of communication that preschool organizations use in working with families and their content. Important aspects of cooperation between the educational institution and the family in the development of the child are analyzed
Keywords: Collaboration; socialization; development; immunological education